2022
DOI: 10.1371/journal.pone.0261821
|View full text |Cite
|
Sign up to set email alerts
|

A platform of assays for the discovery of anti-Zika small-molecules with activity in a 3D-bioprinted outer-blood-retina model

Abstract: The global health emergency posed by the outbreak of Zika virus (ZIKV), an arthropod-borne flavivirus causing severe neonatal neurological conditions, has subsided, but there continues to be transmission of ZIKV in endemic regions. As such, there is still a medical need for discovering and developing therapeutical interventions against ZIKV. To identify small-molecule compounds that inhibit ZIKV disease and transmission, we screened multiple small-molecule collections, mostly derived from natural products, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
(110 reference statements)
1
5
0
Order By: Relevance
“…It has also been shown that addition or enhancement of ECM deposition in neural 2D co-cultures accelerated the formation of neural networks, and in one example, the drug responses were more similar to those obtained in vivo 11,12 , thus reproducing evidence from in vivo experiments that ECM plays an important role in the development and function of the neural circuitry in the brain. Similar data has now also been shown for many non-neuronal 3D tissue models [13][14][15] .…”
supporting
confidence: 81%
“…It has also been shown that addition or enhancement of ECM deposition in neural 2D co-cultures accelerated the formation of neural networks, and in one example, the drug responses were more similar to those obtained in vivo 11,12 , thus reproducing evidence from in vivo experiments that ECM plays an important role in the development and function of the neural circuitry in the brain. Similar data has now also been shown for many non-neuronal 3D tissue models [13][14][15] .…”
supporting
confidence: 81%
“…Since these early developments, multiple oBRB models have used hiPSCs, most frequently derived from dermal fibroblasts [ 65 , 98 , [111] , [112] , [113] , [137] , [138] , [139] ]. The use of hiPSCs has notably enabled the development of multiple disease models by deriving hiPSCs-RPE cells from fibroblasts from patients with retinal diseases [ 58 , 65 , 66 , 98 , 112 , 140 ].…”
Section: Major Considerations About the Obrb Modelsmentioning
confidence: 99%
“…The advantage of using iPSCs has already been mentioned before (section 4.1.1 ). In the case of co-culture models, the ability to obtain both iPSCs derived RPE cells and ECs from the same patient offers the possibility to create disease models for personalized medicine [ 112 , 113 , 139 ]. To our knowledge, only three groups have used hiPSCs-derived ECs, characterized by the expression of CD31, ETV2 and vWF markers [ 112 , 113 , 139 ].…”
Section: Major Considerations About the Obrb Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there are currently few resources available for such work and, in particular, traditional virus titration-based analysis of virus infection is cumbersome and presents a challenge to the use of these viruses in larger-scale applications. For other virus families, the development of reporter-protein-expressing viruses has proven valuable for antiviral drug discovery efforts [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], as well as downstream mechanism of action studies [ 29 , 30 ], and even the identification of host factors required for the viral lifecycle [ 31 , 32 , 33 , 34 ], which can themselves then be leveraged as targets for treatment. Further, for arenaviruses, recent work has shown that the development of reporter protein-expressing arenaviruses is possible [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and some have even been successfully used for high-throughput screening [ 35 , 36 , 44 ].…”
Section: Introductionmentioning
confidence: 99%